St. John's House, Hoxton, with a plan of its environs - Dale; Schnebbelie, Robert Blemmell (Tufts Archival Research Center, 2008)
A farm house for the city and other poor kept by Mr. Thomas Tipple. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.